Odpowiedź :
a) -4(x-2)(x-8)<bądź równe 0
-4(x²-8x-2x+16)<bądź równe 0
-4(x²-10x+16)<bądź równe 0
-4x²+40x-64<bądź równe 0
-4x²+40x-64=0
a=-4 b=40 c=-64
Δ=b²-4ac
Δ=40²-4*(-4)*(-64)
Δ=1600-1024
Δ=576
pier.z Δ=24
x1= -b-pier.z Δ/2a
x1=-40-24/-8 = -64/-8= 8
x2= -b+pier.z Δ/2a
x2= -40+24/-8= -16/-8= 2
b) -x+1/2x+3<0 |-3
-x+1/2x < -3
-1/2x < -3 |*(-2)
x > 6
-4(x²-8x-2x+16)<bądź równe 0
-4(x²-10x+16)<bądź równe 0
-4x²+40x-64<bądź równe 0
-4x²+40x-64=0
a=-4 b=40 c=-64
Δ=b²-4ac
Δ=40²-4*(-4)*(-64)
Δ=1600-1024
Δ=576
pier.z Δ=24
x1= -b-pier.z Δ/2a
x1=-40-24/-8 = -64/-8= 8
x2= -b+pier.z Δ/2a
x2= -40+24/-8= -16/-8= 2
b) -x+1/2x+3<0 |-3
-x+1/2x < -3
-1/2x < -3 |*(-2)
x > 6
![Zobacz obrazek Papupinka](https://pl-static.z-dn.net/files/d30/a5238b27fa4a6089d60de1ba89e6b1ac.jpg)
a)-4(x²-8x-2x+16)≤0
-4x²+32x+8x-64≤0
-4x²+40x-64≤0
delta=1600-1024=576
√576=24
x₁=(-40-24)/-8=8
x₂=(-40+24)/-8=2
x∈<2,8>
-4x²+32x+8x-64≤0
-4x²+40x-64≤0
delta=1600-1024=576
√576=24
x₁=(-40-24)/-8=8
x₂=(-40+24)/-8=2
x∈<2,8>